Integrating Resource Consumption Accounting (RCA) and Risk-Based Costing (RBC) and its Impact on Improving the Accuracy of Cost Measurement and Profitability Analysis under Digital Transformation: An applied Study in Ibn Al-Baytar Specialized Hospital for Cardiac Surgery - Ali Abdul-Hussein Hani Al-Zameli (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research aims to study the impact of integrating Resource Consumption Accounting (RCA) and Risk-Based Costing (RBC) on improving the accuracy of cost measurement and profitability analysis of healthcare services in the context of digital transformation. This is achieved through a practical application at Ibn Al-Baytar Specialized Hospital for Cardiac Surgery. The study stems from the problem of traditional costing systems failing to provide accurate information reflecting the true consumption of resources, as well as neglecting the costs of medical and operational risks associated with providing healthcare services, thus limiting the efficiency of administrative decisions. The research employed a descriptive-analytical approach and an applied approach (case study). The hospital's accounting data was analyzed, medical and non-medical resources were identified, and their consumption rates were measured according to the RCA approach. Additionally, risks associated with medical services were identified and classified, and their costs were allocated according to the RBC approach, utilizing the digital information systems available at the hospital. A comparison was also conducted between the results of the traditional system and the proposed costing model. The research concluded that integrating RCA and RBC significantly contributes to improving the accuracy of healthcare cost measurement, enhances the objectivity of profitability analysis, and supports rational pricing and resource allocation decisions, particularly in the context of digital transformation, which facilitates data collection and analysis.